OPTIMALISASI PEMBELAJARAN ANAK USIA SEKOLAH DASAR MELALUI PEMAHAMAN TEORI PERKEMBANGAN KOGNITIF JEAN PIAGET - Ahsanul Huda Susanto; Murfiah Dewi Wulandari; Darsinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore how to optimize elementary school children's learning through understanding Jean Piaget's cognitive development theory. The research employs a literature review approach and qualitative analysis of relevant literature. The main focus is on the concrete and formal operational stages that influence children's understanding of learning. Data analysis is conducted descriptively to identify the implications of Piaget's theory in designing teaching strategies appropriate to children's cognitive development stages. This study formulates a conceptual framework to support educators in optimizing classroom teaching and learning processes, considering individual differences in thinking and information processing abilities. The findings indicate that optimizing learning through understanding Piaget's theory involves using strategies and methods that align with children's cognitive development stages. The methods used include contextual learning, outdoor learning, group discussions, cooperative learning, inquiry-based learning, and constructivist models, which help children develop critical and logical thinking skills.